2012
DOI: 10.1590/s0036-36342012000700008
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations to improve healthcare of neonates with respiratory insufficiency beneficiaries of Seguro Popular

Abstract: Jasso-Gutiérrez L, Durán-Arenas L,Flores-Huerta S, Cortés-Gallo G. Recommendations to improve healthcare of neonates with respiratory insufficiency beneficiaries of Seguro Popular. Salud Publica Mex 2012;54 suppl 1:S57-S64. AbstractObjective. To evaluate the structure and processes of care of neonatal intensive care units (NICU) providing health care to neonates with respiratory insufficiency, and financed by Seguro Popular. Materials and Methods. A cross-sectional design was used; 21 NICU were included. Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…This result is in agreement with this study [12] who found that neonates who are between (>34 -< 37) weeks gestational age had the highest survival rate followed by neonates who are between (30 -<34) weeks gestational age who had less survival rate than the previous group followed by neonates who are between (27-<30) weeks gestational age who had the least survival rate. Regarding to the duration of ventilation assistance significant difference (p=0.024) was found between survived group and group who died and this result is in agreement with this study [10] who found that (70.37%) of the cases survived needed (1-7) days of ventilation , also in agreement with this study [8] who found that (75.8%) of the cases survived required ventilation for (4)(5)(6)(7) days .This result may be explained by the fact that short period of MV will cause an inflammation cascade in the lungs as showed in this study [13] and this suggests that weaning from MV should be done as soon as possible, in order to prevent pulmonary sequelae and adverse neurodevelopmental outcomes [14]. In this study, survival rate for RDS was (48.3%)and this is in agreement with both studies [7] and [9] While the mortality rate of RDS was the highest compared to other indications of MV and this result is contrary with this study [10] and with this study [11] who reported that the mortality rate for RDS was only 15-25%.…”
Section: Results: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is in agreement with this study [12] who found that neonates who are between (>34 -< 37) weeks gestational age had the highest survival rate followed by neonates who are between (30 -<34) weeks gestational age who had less survival rate than the previous group followed by neonates who are between (27-<30) weeks gestational age who had the least survival rate. Regarding to the duration of ventilation assistance significant difference (p=0.024) was found between survived group and group who died and this result is in agreement with this study [10] who found that (70.37%) of the cases survived needed (1-7) days of ventilation , also in agreement with this study [8] who found that (75.8%) of the cases survived required ventilation for (4)(5)(6)(7) days .This result may be explained by the fact that short period of MV will cause an inflammation cascade in the lungs as showed in this study [13] and this suggests that weaning from MV should be done as soon as possible, in order to prevent pulmonary sequelae and adverse neurodevelopmental outcomes [14]. In this study, survival rate for RDS was (48.3%)and this is in agreement with both studies [7] and [9] While the mortality rate of RDS was the highest compared to other indications of MV and this result is contrary with this study [10] and with this study [11] who reported that the mortality rate for RDS was only 15-25%.…”
Section: Results: Discussionsupporting
confidence: 91%
“…Other reports confirm that respiratory distress is common in neonates and occurs in approximately 7% of babies during the neonatal period [1]. Respiratory disorders are the leading causes of early neonatal mortality (0-7 days of age) [4].…”
Section: Introductionmentioning
confidence: 93%
“…Other reports confirm that respiratory distress is common in neonates and occurs in approximately 7% of babies during the neonatal period [3] , [5] . Respiratory disorders are the leading cause of early neonatal mortality (0–7 days of age) [6] , as well as the leading cause of morbidity in newborns [7] , and are the most frequent cause of admission to the special care nursery for both term and preterm infants [8] . In fact, neonates with respiratory distress are 2–4 times more likely to die than neonates without respiratory distress [9] .…”
Section: Preamblementioning
confidence: 99%
“…For maximal impact, NCCS should include several key policy components, as outlined in Box 1 and detailed below. While examples of such strategies are rare in LMICs, notable exceptions include the recent expansion of Seguro Popular in Mexico, which is used as an illustration throughout this article [17][19].…”
Section: Building National Childhood Cancer Strategiesmentioning
confidence: 99%